Ag/Se‐Catalyzed Selective Epoxidation of β‐Ionone with Molecular Oxygen. Issue 37 (5th October 2022) - Zhang, Xu; Zuo, Tingting; Yu, Lei
Abstract: Ag/Se could be easily fabricated by calcining selenium and silver powders. It was found to be an efficient catalyst for the selective epoxidation of the endocyclic C=C bond of β ‐ionone to produce β ‐ionone epoxide, an important organic intermediate in pharmaceutical industry. It is notable that the reaction can employ molecular oxygen as the cheap, clean and relatively safe oxidant, and no additives such as NHPI are required. The green process makes the method practical for large‐scale application. Abstract : Ag/Se could be easily fabricated by calcining selenium and silver powders. It was found to be an efficient catalyst for the selective epoxidation of the endocyclic C=C bond of β ‐ionone to produce β ‐ionone epoxide, an important organic intermediate in pharmaceutical industry. It is notable that the reaction can employ molecular oxygen as the cheap, clean and relatively safe oxidant, and no additives such as NHPI are required. The green process makes the method practical for large‐scale application.